Self-Inflicted Deprivation? Quality-as-Sent and Quality-as-Received in German News Media - Geiß, Stefan (2020)
Both the news media and citizens have been blamed for citizens’ lack of political sophistication. Citizens’ information source choices can certainly contribute to suboptimal results of opinion formation when citizens’ media menus feature few, redundant, or poor-quality outlets. How strongly news consumers’ choices affect the quality of information they receive has rarely been investigated, however. The study uses a novel method investigating how content-as-sent translates into content-as-received that is applicable to high-choice information environments. It explores quality-as-sent and quality-as-received in a content analysis that is combined with survey data on news use. This study focuses on ‘selection quality’ measured in terms of scope and balance of subtopic units, information units, and protagonist statements sent/received. Regarding quality-as-sent, the scope of news proves to be lowest in TV news and substantially greater for online news and newspapers; imbalance of coverage varies only moderately between outlets. As for quality-as-received, the scope citizens received was only a small fraction of what the news outlets provided in combination or what the highest-quality news outlet provided, but was close to what one average news outlet provided. There was substantial stratification in the extent to which news coverage quality materializes at the recipient level. Scope-as-received grew mainly with using more news, relatively independent of which specific news outlets were used. Imbalance-as-received, however, was a function of the use of specific outlet types and specific outlets rather than the general extent of news use. Using additional news media improved the quality-as-received, invalidating the notion that different news outlets merely provide “more of the same.”